Effect of anti IL-12/23 on body composition: results of bioelectrical impedance analysis in Caucasian psoriatic patients. (4th March 2018) - Galluzzo, Marco; D'Adamio, Simone; Pastorino, Roberta; Andreoli, Angela; Servoli, Stella; Bianchi, Luca; Talamonti, Marina
ABSTRACT: Background : Bioelectrical impedance analysis (BIA) is an inexpensive, non-invasive and fast method to assess body composition. Little is known of the interaction between anti IL 12/23 treatment and body composition. The aim of this study was to evaluate 6- and 12-month changes in body weight, Body Mass Index (BMI) and body composition assessed by BIA in psoriatic patients treated with anti-IL-12/23. Research design and methods : Demographic and clinical data were collected for each enrolled patient. Physical examination, anthropometric assessment, Psoriasis Area and Severity Index (PASI) assessment and body composition by BIA (single-frequency 50 kHz), were assessed at baseline and at 6 and 12 months of treatment. Results : A significant decrease in body weight, compared to baseline, in BMI, Fat Mass at month 6 and a significant increase at month 12 for body cellular mass (BCM) and Phase Angle (PhA) were observed. In addition, a significant increase was found for intracellular water. Conclusion : At baseline, psoriatic patients showed a lower BCM and a lower mean PhA score. During ustekinumab treatment, the mean PhA and BCM scores increased with an improvement in psoriatic disease. Thus, ustekinumab can be an effective drug for improving not only psoriasis but also the general clinical status of patients.